IMPLEMENTATION OF INTEGRATED MARKETING COMMUNICATIONS ON THE MARKET OF TOURIST SERVICES - Rybchuk , A.V.; Zhurba , I.E.; Zinkevich , V.I.; Tymoshchuk , O.O. (The actual problems of regional economy development, 2023)
The article analyzes the methodological foundations of the concept of forming a system of integrated marketing communications, the internal logic of their evolutionary development and the expediency of using tourism market entities in global practice. The vector and dominants of the modern development of the system of integrated marketing communications are identified as strategically significant landmarks of their evolution. The content of the economic nature of marketing communications is disclosed in the coordinates of the general theory of marketing within the framework of system-functional analysis, which provides research into the genesis of the system of integrated marketing communications in tourist companies. It is noted that the formation of a system of modern marketing communications in the conditions of various interactions of modern tourism companies with consumers, clients, partners and competitors is achieved through the creation of sustainable competitive advantages due to goal-oriented marketing communications with the dominance of integration trends. It is emphasized that effective marketing decisions when promoting a tourist product to the market are based on the economic content of the nature of marketing communications in tourism. It is shown that the main result of the creation of integrated marketing communications is a synergistic effect, which determines the interaction of tourism market subjects, which are included in communications, activating the potential of their action. It is noted that the principles of efficiency and personalization, quick response to the requirements of the tourist market are important in the conditions of dynamic market competition. It has been confirmed that the marketing mechanism of strategic management of the communication policy of promoting the tourist product will allow active stimulation of consumers to increase the volume and frequency of consumption of tourist services and convince potential consumers to maintain continuous communication through the proposed toolkit of integrated marketing communications.